Testing the Use of Forest Soil δ13C Shifts as a Post-Fire Index for Soil Burn Severity Estimation - Irene Fernandez; Ana Cabaneiro (Proceedings, 2020)
Due to the increasing number and virulence of forest wildfires recently observed around the world, the establishment of a simple, accurate and reliable index that would correctly evaluate the fire effects on soil quality as a support for a suitable forest recovery management is becoming progressively more necessary. This objective is addressed here by using both δ13C isotope ratio mass spectrometry and traditional solvent fractionation methods (widely used to assess soil biogenic components or humus fractions) to quantify the temperature-induced changes in soil chemical and isotopic composition. Soil samples from the upper 5 cm layer of two Cambisols developed over granite under pine forest in the NW of Spain were heated in an oven under controlled conditions to attain moderate or intense soil burn severity levels by using two different temperatures (220 °C or 350 °C). Biochemical changes induced by the heating process appreciably differed according to the intensity of the temperature applied. Multilinear regression modelling not only showed a significant relationship between soil C isotopic signature shifts (Δsoil δ13C) with temperature increases but also revealed other key outcomes: i.e., >96 or >81% of its total variance can be predicted by changes in lignin or non-humified organic matter, respectively. Indeed, Δsoil δ13C explained by itself ≈60% of thermal variance, pointing to the aptness of using 13C shifts as a valid index for soil burn severity estimation in wildfires.